Cancer‐associated fibroblasts promote tumor progression by lncRNA‐mediated RUNX2/GDF10 signaling in oral squamous cell carcinoma. Issue 3 (10th June 2021) - Zhang, Dongya; Song, Yuxian; Li, Dan; Liu, Xinghan; Pan, Yuchen; Ding, Liang; Shi, Guoping; Wang, Yong; Ni, Yanhong; Hou, Yayi
Abstract : Cancer‐associated fibroblasts (CAF) are the most abundant stromal cells in tumor and exert a pro‐tumoral effect in cancer progression. Numerous evidence shows long non‐coding RNA (lncRNA) abnormally regulates gene expression in various cancers. However, little is known about the role of lncRNA in the interaction between CAF and cancer cells. Here, we first identify an uncharacterized lncRNA, LOC100506114, which is significantly upregulated in CAF and is involved in the functional transformation of normal fibroblasts (NF) and CAF. Expression of LOC100506114 enhances the expression of fibroblast activation protein alpha and α‐smooth muscle actin in NF and promotes malignant characteristics of NF and CAF in vivo and in vitro . The profile of gene co‐expression analysis shows that growth differentiation factor 10 (GDF10) is positively correlated with the expression of LOC100506114. CAF promote stromal fibroblast activation and the proliferation and migration of tumor cells by secreting GDF10. Our data demonstrate that lncRNA plays a critical role in the interplay of stromal fibroblasts and tumor cells in oral squamous cell carcinoma. Abstract : Abnormal expression of lncRNA LOC100506114 in oral squamous cell carcinoma (OSCC) induced normal fibroblasts (NF) to transform into CAF by upregulating growth differentiation factor 10 (GDF10) expression and secretion. The interaction of GDF10 with the transcription factor RUNX family transcription factor 2 further enhanced the growth and migration of OSCC tumor cells by activating the TGFβRI/Smad3/ERK pathway. Our results demonstrate that lncRNA play an important role in the functional transformation of human NF into CAF and promote OSCC tumorigenesis.